2020
DOI: 10.1096/fj.201903266rr
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic necrotizing factor 1 promotes bladder cancer angiogenesis through activating RhoC

Abstract: Uropathogenic Escherichia coli (UPEC), a leading cause of urinary tract infections, is associated with prostate and bladder cancers. Cytotoxic necrotizing factor 1 (CNF1) is a key UPEC toxin; however, its role in bladder cancer is unknown. In the present study, we found CNF1 induced bladder cancer cells to secrete vascular endothelial growth factor (VEGF) through activating Ras homolog family member C (RhoC), leading to subsequent angiogenesis in the bladder cancer microenvironment. We then investigated that C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
15
1
Order By: Relevance
“…cnf is a cyclomodulin that promotes cellular proliferation by stimulating the assembly of actin stress fibers and focal adhesions by deamination and DNA synthesis, and cnf has only been found in E. coli and Y. pseudotuberculosis. Although cnf has been associated with uropathogenic E. coli and bladder cancer, in this study, cnf was found in DEC and non-DEC, and primarily in CRC patients [26]. A previous report detected cnf-1 in stool samples for the first time, but only one sample was positive for this genotoxin from healthy people in Puerto Rico.…”
Section: Discussioncontrasting
confidence: 60%
“…cnf is a cyclomodulin that promotes cellular proliferation by stimulating the assembly of actin stress fibers and focal adhesions by deamination and DNA synthesis, and cnf has only been found in E. coli and Y. pseudotuberculosis. Although cnf has been associated with uropathogenic E. coli and bladder cancer, in this study, cnf was found in DEC and non-DEC, and primarily in CRC patients [26]. A previous report detected cnf-1 in stool samples for the first time, but only one sample was positive for this genotoxin from healthy people in Puerto Rico.…”
Section: Discussioncontrasting
confidence: 60%
“…In most studies, the induction of at least some of the morphological effects characteristic of Rho GTPase activation is described, that is, changes in the actin cytoskeleton organization, demonstrated by actin stress fibers or the formation of actin cables, membrane ruffles, filopodia and lamellipodia assembly (Figure 2A) [6][7][8]10,25,26,32,[34][35][36]38,40,41,[44][45][46][47][50][51][52]56,94,95]. Regardless of the method used to identify the impact of CNF1-induced cytoskeletal modifications on cell movement ability (migration-invasion test, scratch wound healing assay), CNF1 treatment stimulated an increase of cell motility in 13 cell lines (T24, 5637, HUVEC [28]; HT-29, SW480, HEp-2 [22]; PC3, LNCaP, 22Rv1, VCaP [62]; BL6-10 [64]; 804G, HUVEC [8]; T-lymphocytes [44]). Among these, in PC3 [62] and BL6-10 [64] cells, this effect was accompanied by an in vivo increase in metastatic ability.…”
Section: Effects On Rho Gtpases and On Actin Cytoskeletonmentioning
confidence: 99%
“…Both Rho GTPases and cytoskeletal rearrangements are also known to influence gene transcription [93]. Actually, after CNF1 intoxication, in 17 cell lines (HeLa [38]; BL6-10 [65]; HEp-2 [48,52]; GL-261 [31]; C2C12 [76]; HUVEC [10]; 3T3-L1 [75]; mouse peritoneal macrophages, Raw264.1, BMDM, THP-1 [96]; 5637, T24 [28]; HT-29, IEC-6 [22]; 293T [68]) a number of transcription factors (TFs) also result in being modulated. For example, in HEp-2 epithelial cells, CNF1 activates NF-κB through the Rac1/PI3K/Akt/IKK prosurvival pathway, with the ensuing modulation of the antiapoptotic proteins Bcl-2 and Bcl-XL [51,95].…”
Section: Cnf1 Effects On Different Cellular Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoC reportedly affects cell movement by influencing the activities of actin and myosin, and cell adhesion [ 35 ], thereby affecting the process of cancer metastasis. According to the existing literature, it plays an important role in many cancers, such as influencing angiogenesis in bladder cancer [ 36 ] and tumorigenesis and epithelial-mesenchymal transition (EMT) in osteosarcoma [ 37 ], regulating the emergence of radioresistance in cervical cancer [ 38 ], and affecting prostate cancer treatments that target the glutamine pathway [ 39 ]. Certainly, its most significant role is promoting metastasis in breast [ 40 42 ], gastric [ 43 , 44 ], colon [ 45 , 46 ], bladder [ 47 ], prostate [ 48 , 49 ], lung [ 50 ], pancreatic [ 51 ], liver [ 52 ] and other cancers.…”
Section: Introductionmentioning
confidence: 99%